Calcium deficiency worldwide: prevalence of inadequate intakes and associated health outcomes. Issue 1 (5th March 2022) - Shlisky, Julie; Mandlik, Rubina; Askari, Sufia; Abrams, Steven; Belizan, Jose M.; Bourassa, Megan W.; Cormick, Gabriela; Driller‐Colangelo, Amalia; Gomes, Filomena; Khadilkar, Anuradha; Owino, Victor; Pettifor, John M.; et al.
Abstract: Dietary calcium deficiency is considered to be widespread globally, with published estimates suggesting that approximately half of the world's population has inadequate access to dietary calcium. Calcium is essential for bone health, but inadequate intakes have also been linked to other health outcomes, including pregnancy complications, cancers, and cardiovascular disease. Populations in low‐ and middle‐income countries (LMICs) are at greatest risk of low calcium intakes, although many individuals in high‐income countries (HICs) also do not meet recommendations. Paradoxically, many LMICs with lower calcium intakes show lower rates of osteoporotic fracture as compared with HICs, though data are sparse. Calcium intake recommendations vary across agencies and may need to be customized based on other dietary factors, health‐related behaviors, or the risk of calcium‐related health outcomes. The lack of standard methods to assess the calcium status of an individual or population has challenged efforts to estimate the prevalence of calcium deficiency and the global burden of related adverse health consequences. This paper aims to consolidate available evidence related to the global prevalence of inadequate calcium intakes and associated health outcomes, with the goal of providing a foundation for developing policies and population‐level interventions to safely improve calcium intake and status where necessary. Abstract : This paper aims to consolidate available evidence related to the global prevalence of inadequate calcium intakes and associated health outcomes, with the goal of providing a foundation for developing policies and population‐level interventions to safely improve calcium intake and status where necessary.